Efektivitas Pengapuran dalam Meningkatkan Pertumbuhan dan Produksi Tanaman Sorgum (Sorghum bicolor (L.) Moench) sebagai Hijauan Pakan Ternak - Iwan Prihantoro; Asep Tata Permana; Suwarto Suwarto; Edit Lesa Aditia; Yualisna Waruwu (Institut Pertanian Bogor, 2023)
Sorghum is a potential crop as feed forage. The objective of the research was to obtain optimum dose of liming to improve the growth and productivity of sorghum (Sorghum bicolor (L.) Moench) biomass as feed forage. A completely randomized design with 4 treatments and 4 replications were applied for the research. The treatments were doses of dolomite lime addition i.e., 1) SD0 (dolomite lime addition at a dose of 0 ton/ha) as a control, 2) SD1 (dolomite lime addition at a dose of 1 ton/ha), 3) SD2 (dolomite lime addition at a dose of 2 ton/ha), and 4) SD3 (dolomite lime addition at a dose of 3 ton/ha). The result shows that supplementation of dolomite lime at doses of 2‒3 tons ha-1 can increase soil pH after a week of incubation. The dolomite lime addition at a dose of 3 tons ha-1 significantly increases (P<0.05) the plant height (2 weeks after planting) and the number of leaves from a week after planting until the end of the research (10 weeks after planting). In addition, this dose of dolomite addition (3 tons/ha) can increase fresh biomass productivity as well as dry biomass compared to control (SD0). In conclusion, supplementation of dolomite lime at a dose of 3 tons ha-1 was effective to increase the pH value of soil, plant height, leaves number, as well as fresh and dry biomass of sorghum plant. In addition, this dose of dolomite lime produces better green color of sorghum plant leaf compared to without liming. Keywords: biomass production, dolomite lime, feed forage, Sorghum bicolor (L.) Moench